Corrosion Prevention on Coated Rebars and Fiber in R.C Slabs - M.Tamil Selvi, Dr; J Hathari Evangalin, Ms.; S. Gayathri, M.s (International Journal of Engineering and Technology, 2018)
Concrete structures prevail primarily due to prior attrition of steel due to preterm failure of rebars. The major cause of deterioration is the corrosion of the steel reinforcement, that can lead to structural problems. By utilizing our knowledge on corrosion of steel reinforcement, concrete structures could be made more durable. The research work is intend at arrestcorrosion in RC slabs by glazing silicon tombac to the steel rods. Nylon fiber is induced in concrete to attain strength for the concrete. A study report carried the effects of coating material between the conventional and fibers in concrete was compared with that of uncoated material between the conventional and fiber in concrete rebarâ€™s. A continuous corrosion process is accelerated by inducing direct current to rebars. Process used to prompt corrosion is Accelerated corrosion test and Half-cell measurement.Â Â